Government efficiency and international technology adoption: The spread of electronic ticketing among airlines - Galang, Roberto Martin N (Journal of International Business Studies, 2012)
Extending research on the institution-based view of international business strategy, this paper posits that the international adoption of technology among firms is distinct from its intra-national counterpart because this process is influenced by the efficiency of the government institutions where each firm is located. Low government efficiency delays investment in unknown technologies by increasing contracting hazards, environmental uncertainty and the difficulty of allocating potential returns; thus requiring greater experience on the part of firms when undertaking investment decisions. Furthermore, government inefficiency accentuates the relative significance of firm-specific drivers of technology adoption, but reverses the positive effect of industry competition in promoting technology adoption. I empirically investigate this phenomenon through hazard models analyzing the factors that affect the timing of the adoption of electronic ticketing by close to 180 airlines operating in 110 different countries. The results imply that government inefficiency in certain countries not only leads to slower technology penetration rates compared with their counterparts, but also exacerbates the technology gaps within countries by providing unwarranted advantages to firms that are already well entrenched.